Empirical modelling of the solar spectral influence on photovoltaic devices for improved performance forecasting - Daxini, Rajiv (2024)
Photovoltaic performance modelling is essential for the successful development of PV systems. Accurate modelling can inform system design and financing prior to construction, help with fault detection during operation, and improve the grid penetration of PV energy.